Early time course of change in angiogenic proteins in human skeletal muscle and vascular cells with endurance training. (20th April 2020) - Hoier, Birgitte; Olsen, Karina; Hanskov, Dorte J. A.; Jorgensen, Maria; Norup, Liselotte R.; Hellsten, Ylva
Abstract : Angiogenic, mitochondrial, and related transcriptional proteins were assessed in human skeletal muscle and isolated vascular cells during the early phase of endurance training. Thigh muscle biopsies were obtained in healthy young subjects, after one acute bout (n = 9) and after 3, 5, 7, and 14 days (n = 9) of cycle ergometer training. Whole muscle homogenates were analyzed for angiogenic, mitochondrial, and regulatory mRNA and protein levels. Angiogenic proteins were determined in muscle‐derived endothelial cells and pericytes sorted by fluorescence‐activated cell sorting. Acute exercise induced an increase in whole muscle mRNA of peroxisome proliferator‐activated receptor gamma coactivator 1α (4.5‐fold; P  = .002) and vascular endothelial growth factor (VEGF) (2.4‐fold; P  = .001) at 2 hours post. After 14 days of training, there was an increase in CD31 protein (63%; P  = .010) in whole muscle indicating capillary growth. There was also an increase in muscle VEGF receptor 2 (VEGFR2) (1.5‐fold; P  = .013), in OXPHOS proteins (complex I, II, IV, V; 1.4‐ to 1.9‐fold; P  < .05) after 14 days of training and an increase in estrogen‐related receptorα protein (1.5‐fold; P  = .039) at 14 days compared to 5 days of training. Both endothelial cells and pericytes expressed VEGF and other angiogenic factors at the protein level but with a distinctively lower expression of VEGFR2 and thrombospondin‐1 (TSP‐1) in pericytes. The findings illustrate that initiation of capillary and mitochondrial adaptations occurs within 14 days of training and suggest that sustained changes in angiogenic proteins including VEGF and TSP‐1 are moderate in whole muscle and vascular cells.